Development Model of Basic Principles of Consumption in an Islamic Microeconomic Perspective - Asep Dadang Hidayat; Chandra; Mohamad Anton Athoillah (al-Afkar, Journal For Islamic Studies, 2023)
The activity of fulfilling basic needs that humans need, one of which must make a sacrifice by giving up something of value or value for something they want. The activity in question that humans commonly do is buying and selling. Islam views the concept of buying and selling as a tool to make humans more mature in thinking and carrying out various economic activities. This research aims to answer, describe and analyse the Object of Consumption, Assumptions of Consumer Behaviour, and Principles of Consumer Behaviour, as well as Consumer Satisfaction Criteria. The research method used is a literacy study or library research. The results of this study indicate that: Consumption is not just an activity of eating or drinking, but is an activity in using goods or services that can directly satisfy individual human needs. Thus consumption can be concluded as an activity to fulfil needs in order to achieve satisfaction, Consumption assumptions must prioritise aspects of morality and social responsibility, Consumption is at least controlled by five principles, namely: Justice, cleanliness, simplicity, generosity and morality, factors that affect consumer satisfaction: Product, service, emotional, cost and price.